2020
DOI: 10.1101/2020.02.18.954693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing the Fate of Brain Metastatic Breast Cancer Cells in Different Immune Compromised Mice with Cellular Magnetic Resonance Imaging

Abstract: 25Metastasis is the leading cause of mortality in breast cancer patients, with brain metastases becoming increasingly 26 prevalent. Studying this disease is challenging due to the limited experimental models and methods available. Here, 27 we used iron-based cellular MRI to track the fate of a mammary carcinoma cell line (MDA-MB-231-BR) in vivo to 28 characterize the growth of brain metastases in the nude and severely immune-compromised NOD/SCID/ILIIrg-/-29 (NSG) mouse. 30Nude and NSG mice received injections … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The addition of the magnetic plate for labeling was likely ineffective due to the fact that the majority of these cells are in suspension during labeling, which differs from most studies which have labeled adherent cells. Previous work by our group has shown that this concentration of MPIO effectively labels immortalized cancer cells for the purposes of cell tracking (38), however, the methods of labeling described in this work varies from the traditional labeling protocol of adherent cells due to the differences in homogeneity and complex cell culture required to grow PDX cells. Future work will investigate labeling trials with different iron particles and whether this changes the visualization of these cells in vivo with MPI or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the magnetic plate for labeling was likely ineffective due to the fact that the majority of these cells are in suspension during labeling, which differs from most studies which have labeled adherent cells. Previous work by our group has shown that this concentration of MPIO effectively labels immortalized cancer cells for the purposes of cell tracking (38), however, the methods of labeling described in this work varies from the traditional labeling protocol of adherent cells due to the differences in homogeneity and complex cell culture required to grow PDX cells. Future work will investigate labeling trials with different iron particles and whether this changes the visualization of these cells in vivo with MPI or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the magnetic plate for labeling was likely ineffective due to the fact that the majority of these cells are in suspension during labeling, which differs from most studies which have labeled adherent cells. Previous work by our group has shown that this concentration of MPIO effectively labels immortalized cancer cells for the purposes of cell tracking [ 30 ]. However, the methods of labeling described in this work varies from the traditional labeling protocol of adherent cells due to the differences in homogeneity and complex cell culture required to grow PDX cells.…”
Section: Discussionmentioning
confidence: 99%